The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1016/j.joca.2004.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent treatment of knee osteoarthritis with oral chondroitin sulfate: a one-year, randomized, double-blind, multicenter study versus placebo11Principal Investigators: D. Uebelhart, MD, Assistant Professor; M. Malaise, MD, Professor, R. Marcolongo, MD, Professor; E. Vignon, MD, Professor. Co-Investigators: M. Piperno, MD, Head Physician; E. Mailleux, MD, Head Physician; A. Fioravanti, MD, Head Physician; L. Matoso, MD, Physician; Statistical analysis: F. DeVathaire, PhD, Professor; Radiological analy

Abstract: This study provides evidences that oral CS decreased pain and improved knee function. The 3-month intermittent administration of 800mg/day of oral CS twice a year does support the prolonged effect known with symptom-modifying agents for OA. The inhibitory effect of CS on the radiological progression of the medial femoro-tibial joint space narrowing could suggest further evidence of its structure-modifying properties in knee OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(48 citation statements)
references
References 25 publications
4
42
0
2
Order By: Relevance
“…Most studies had a sample size larger than 50 participants; in particular, several studies had sample sizes of 100 or more (Alekseeva 1999; Alekseeva 2005a; Alekseeva 2008; Clegg 2006; Gabay 2011; Kahan 2009; L’Hirondel 1992; Mazieres 2001; Michel 2005; Moller 2010; Morreale 1996; Nasonova 2001; Pavelka 1999; Pavelka 2010; Rai 2004; Sawitzke 2008; Sawitzke 2010; Uebelhart 2004; Fardellone 2013). …”
Section: Resultsmentioning
confidence: 99%
“…Most studies had a sample size larger than 50 participants; in particular, several studies had sample sizes of 100 or more (Alekseeva 1999; Alekseeva 2005a; Alekseeva 2008; Clegg 2006; Gabay 2011; Kahan 2009; L’Hirondel 1992; Mazieres 2001; Michel 2005; Moller 2010; Morreale 1996; Nasonova 2001; Pavelka 1999; Pavelka 2010; Rai 2004; Sawitzke 2008; Sawitzke 2010; Uebelhart 2004; Fardellone 2013). …”
Section: Resultsmentioning
confidence: 99%
“…Authors concluded that oral chondroitin sulphate is an effective and safe symptomatic slow-acting drug for the treatment of knee OA and, in addition, CS might be able to stabilise the joint space width and can modulate bone and joint metabolism. Again Uebelhart et al [84] investigated the efficacy and tolerability of a 3-month duration, twice a-year, intermittent treatment with oral chondroitin sulphate in knee osteoarthritis patients with support to previous results.…”
Section: Human Studiesmentioning
confidence: 85%
“…The efficacy of CS in OA treatment has been confirmed by several clinical trials [54][55][56][57][58][59][60][61][62][63][64][65] and reviewed in [66 and 67]. CS efficacy and tolerance ( Table 1) was evaluated in the therapy of tibiofibular arthritis of the knee [54] in forty patients suffering from this illness, and Oliviero et al [55] conducted a clinical trial, lasting 6 months, performed on two hundred patients.…”
Section: Cs In the Treatment Of Oamentioning
confidence: 96%
“…In the CS-treatment group, a significant decrease in the number of patients with new erosive OA was seen. In a very recent randomized, double-blind, multicenter study [63], the efficacy and tolerability of oral CS (Condrosulf ® ) in knee OA patients in a 3-month duration, twice a-year, intermittent treatment was investigated. A total of 120 patients with symptomatic knee OA were randomized into two groups receiving either 800 mg CS or placebo per day for two periods of 3 months during 1 year.…”
Section: Cs In the Treatment Of Oamentioning
confidence: 99%